2003
DOI: 10.1113/jphysiol.2003.053371
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathway of nitric oxide in synaptic GABA release in the rat paraventricular nucleus

Abstract: In the paraventricular nucleus (PVN) of the hypothalamus, nitric oxide (NO) inhibits sympathetic outflow through increased GABA release. However, the signal transduction pathways involved in its action remain unclear. In the present study, we determined the role of cGMP, soluble guanylyl cyclase, and protein kinase G in the potentiating effect of NO on synaptic GABA release to spinally projecting PVN neurones. The PVN neurones were retrogradely labelled by a fluorescent tracer injected into the thoracic spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 44 publications
8
68
1
1
Order By: Relevance
“…guanylyl cyclase | vesicular GABA transporter | BacTRAP | spiny projecting neurons | axon collaterals T hroughout the CNS, the volume transmitter nitric oxide (NO) has been implicated in modulating synaptic function, including transmitter release and plasticity (1,2). The primary target of NO is soluble guanylyl cyclase (sGC), a heterodimer comprising α and β subunits.…”
mentioning
confidence: 99%
“…guanylyl cyclase | vesicular GABA transporter | BacTRAP | spiny projecting neurons | axon collaterals T hroughout the CNS, the volume transmitter nitric oxide (NO) has been implicated in modulating synaptic function, including transmitter release and plasticity (1,2). The primary target of NO is soluble guanylyl cyclase (sGC), a heterodimer comprising α and β subunits.…”
mentioning
confidence: 99%
“…Considering 100 μM of SNAP perfused into the recording chamber, NO may also affect other pathways. A previous study using patch methods has shown that 100 μM SNAP increases GABA release from presynaptic sites through sGCcGMP-protein kinase G in the hypothalamic slice (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…1G&H), indicating that no desensitization to SNAP had occurred. Finally, on the basis of previous reports (Li et al 2003;Wang et al 2006) 20 μM of ODQ, the soluble guanylate cyclase (sGC) inhibitor, was perfused into the recording chamber for 20 min (Fig. 1J&K, n=6).…”
Section: Effect Of No On Gabaergic Mipscsmentioning
confidence: 99%
“…The scientific literature does contain evidence for interaction between GABA and NO, but the majority of such studies focus on NO modulation of the neuronal release of GABA (Wall, 2003;Li et al, 2004). However, a recent study demonstrated that activation of GABA A receptors by muscimol or activation of the benzodiazepine binding site by diazepam increases the population of nNOSpositive cells in the frontal and parietal areas of the developing cortex (Mantelas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%